Selection of circuit and technical solutions for improvement the quality of electricity in adaptive networks with traction AC power - N. V. Savina; I. A. Lisogurskiy; L. N. Lisogurskaya (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Analysis of existing circuit and technical solutions for improving the quality of electricity in networks with traction load and assessment of their compliance with new properties of the electric network when switching to an active adaptive platform. Determination of the features of the operation of electric networks with traction load during the transition to an active-adaptive platform. Review of existing technical means and circuit solutions for improving the quality of electricity in electric networks with traction load and their analysis for compliance with new properties of the electric network.METHODS. To solve the tasks set, a structural analysis of existing technical and circuit solutions was performed to improve the quality of electricity in electric networks with traction load.RESULTS. In this article, the systematization of the compliance of technical means with the solved problems in the field of electricity quality is carried out. The features of the operation of electric networks with traction load during the transition to an active-adaptive platform are determined. Modern technical means and circuit solutions corresponding to the new properties of the electrical network are revealed. A variant of combining technologies for a complex effect on the quality of electricity is proposed.CONCLUSION. When switching electric networks with traction load to an active adaptive platform in order to improve the quality of electricity, it is advisable to use technical means capable of providing PCE within acceptable limits in real time, depending on the operating modes of the power system and traction load. Such means include distributed generation, electric energy storage, active filter-compensating and balancing devices, FACTS technologies of the second generation. Classical approaches to solving problems with the quality of electrical energy based on the use of passive technical devices do not correspond to the new properties of active-adaptive networks with alternating current traction.